Analisis Komunikasi Pemasaran Terpadu Terhadap Perilaku Konsumen - Dewantara, Norman; Noer, Lissa Rosdiana (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2025)
Integrated marketing communication (IMC) has seen rapid development in marketing communication research. This study explores the role of IMC in consumer behaviour. The data collection process used the PRISMA protocol, identifying 60 relevant articles. Data analysis showed that research on this topic has been conducted from 2016 to 2024, with the United States, the United Kingdom, and Poland being the countries conducting the most studies. The most productive researchers were Mohr, I., Mahmoud, A.B., Hack-Polay, D., Grigoriou, N., Fuxman, L., Duralia, O., and Andreoli, T.P., each with two publications. The journal *Cogent Business and Management* contributed the most to IMC research on consumer behavior, with 12 publications. Based on a systematic literature review, IMC supports brand loyalty through innovative communication, enabling more holistic and effective consumer experiences across various channels. The study also highlights the importance of ethical considerations in marketing campaigns to avoid stereotypes or biases.